Trade Size and Information-Motivated Trading in the Options and Stock Markets - Lee, Jason; Yi, Cheong H. (Journal of Financial and Quantitative Analysis, 2001)
This study investigates the extent of information-motivated trading conditional on trade size in the options and stock markets. We find envidence that the options market is the primary venue for information trading only for small investors, whereas large ivestors do not necessarily trade options rather than stocks when they are informed. With different trading mechanisms in the stock and options markets, this finding implies that investors, when facing different impediments to information-related trading, select different vehicles to exploit their information. We also show that the adverse selection component of the bid-ask spread decreases with option delta, implying that options with greater finanical leverage attract more informed investors. Overall, our results reinforce the notion that the options market is a venue for information-motivated trading.